Control applications of nonlinear programming : proceedings of the IFAC workshop, Denver, Colorado, USA, 21 June 1979 - Rauch, H. E. (Herbert E.) (IFAC conference proceedings., 1980)
Control Applications of Nonlinear Programming contains the proceedings of the International Federation of Automatic Control Workshop on Control Applications of Nonlinear Programming, held in Denver, Colorado, on June 21, 1979. The workshop provided a forum for discussing the application of optimal and nonlinear programming techniques to real-life control problems. The volume covers a variety of specific applications ranging from microprocessor control of automotive engines and optimal design of structures to optimal aircraft trajectories, system identification, and robotics.Comprised of 14 cha.